2018
DOI: 10.3384/lic.diva-148074
|View full text |Cite
|
Sign up to set email alerts
|

On Timing-Based Localization in Cellular Radio Networks

Abstract: This is a Swedish Licentiate's Thesis. Swedish postgraduate education leads to a Doctor's degree and/or a Licentiate's degree. A Doctor's Degree comprises 240 ECTS credits (4 years of full-time studies). A Licentiate's degree comprises 120 ECTS credits, of which at least 60 ECTS credits constitute a Licentiate's thesis. Linköping studies in science and technology. Thesis No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…While the joint ToA and DoA algorithm is presented in [5]. The per-formance of LTE positioning over typical multipath fading channels is considered in [8,9] while the error analysis in the position estimation by resolving the first arrival path of the channel is presented in [10,11]. It was shown that using the first path detection improves the positioning performance in multipath fading environment, however; the effect of LTE system and OTDoA parameters on the mitigation of performance deterioration due to channel selectivity is not identified.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…While the joint ToA and DoA algorithm is presented in [5]. The per-formance of LTE positioning over typical multipath fading channels is considered in [8,9] while the error analysis in the position estimation by resolving the first arrival path of the channel is presented in [10,11]. It was shown that using the first path detection improves the positioning performance in multipath fading environment, however; the effect of LTE system and OTDoA parameters on the mitigation of performance deterioration due to channel selectivity is not identified.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The time index of the earliest detected peak in the correlation profile, which corresponds to ToA of the signal travelling through direct propagation path can be estimated by searching for the maximum of the correlation profile as [2,9] ( )…”
Section: Signal Modelmentioning
confidence: 99%